The effect of diet and lipoprotein levels on cardiovascular disease in Karachi - Ullah, Shakir (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Malnutrition and high lipoprotein level have a significant relationship with cardiology, as it can increase the risk of cardiovascular disease (CVD) and exacerbate outcomes in patients with existing CVD. This research aimed to assess the effect of diet and lipoprotein levels on cardiovascular disease in Karachi of Aged 30-60 Years. In this cross-sectional study conducted from January 2023 to April 2024. The participants´ dietary intake, physical activity, body mass index, fat mass, blood pressure, fasting blood glucose, and serum lipid profile were analyzed in the current study. A Questionnaire was used to assess physical activity and a structured 24-hour food-recall questionnaire was used to assess the participants´ dietary intake and exercise or physical activity was recorded on two separate days. Results: A total of 640 individuals were enrolled in the study. All persons had complete participation, filling out two separate 24-hour food-recall questionnaires. The number of females was 320 and similarly, the males were 320. Most of them were married, had an education level less than high school, in physical activity most of the higher-aged people were not involved remained in rest conditions, and were living in urban regions. Their dietary intakes of were contained regularly based on a balanced diet. The vegetable intake was also not proper. Based on age groups, they were divided into five groups marital status, education level, based on region, physical activity, and dietary information were properly recorded. Observing variables (age, gender, physical activity, and daily intake of food groups) showed that more physiological risk factors for CVD revealed that daily intake of a balanced diet, and regular exercise had a significant association with having physiological risk factors of CVD. Based on the current study, it is concluded that most middle-aged (40-50 years) aged people in urban areas, had one to four physiological risk factors for cardiovascular disease and daily intakes of carbohydrates and protein were higher than dietary reference intakes for adults. Conclusion: We also found that the relationship of low physical activity with physiological risk factors for CVD was more substantial than the intake of different food groups. It is also observed that the females had more risk factors for CVD than the males. More relation were found between nutritional status, high lipoprotein level and CVD. The people of Karachi must change their lifestyle of exercise and diet to reduce this main health issue of CVD.